O Museu de Arte da Pampulha e o Palácio das Artes: os equipamentos culturais e a difusão da arte em Belo Horizonte - Baldow, Juliane Guimarães (2020)
In order to raise and discuss the relationship between art and architecture in the city of Belo Horizonte, this work goes through modernity in the capital of Minas Gerais, the formation of its modern cultural equipment until reaching at the neo-avant-garde exhibitions of the 1960’s. A path structured by concepts and theories referring to the modern space and constantly confronted by the singularity of the works of the architect Oscar Niemeyer - the Museum of Art of Pampulha and the Palace of the Arts - objects of this study. The relationships traced seek to question the function of modern space. As a receiver and diffuser of art.